2010
DOI: 10.1186/1471-2474-11-271
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases 1, 3, and 9 in degenerated long head biceps tendon in the presence of rotator cuff tears: an immunohistological study

Abstract: BackgroundLong head biceps (LHB) degeneration, in combination with rotator cuff tears, can be a source of chronic shoulder pain. LHB tenotomy reduces pain and improves joint function although the pathophysiological context is not well understood. Tendon integrity depends on the extracellular matrix (ECM), which is regulated by matrix metalloproteinases (MMP). It is unclear which of these enzymes contribute to LHB but we chose to study MMP 1, 3, and 9 and hypothesized that one or more of them may be altered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…43 The location and size of rotator cuff tears may affect MMP biology, given that degenerated long head of the biceps samples taken from patients with articular-sided partial-thickness rotator cuff tears had higher levels of MMP-1 and MMP-9 compared with patients with partial tears on the bursal side. 33 In contrast, MMP-3 was found to be downregulated.…”
Section: Gene Changes Related To Ecm Remodelingmentioning
confidence: 89%
“…43 The location and size of rotator cuff tears may affect MMP biology, given that degenerated long head of the biceps samples taken from patients with articular-sided partial-thickness rotator cuff tears had higher levels of MMP-1 and MMP-9 compared with patients with partial tears on the bursal side. 33 In contrast, MMP-3 was found to be downregulated.…”
Section: Gene Changes Related To Ecm Remodelingmentioning
confidence: 89%
“…This force balance disruption may lead to humeral head translations (Keener et al, 2009; Oh et al, 2011) and therefore increase the patient’s risk of developing secondary joint damage, such as tear propagation, long head of the biceps (LHB) degeneration (Lakemeier et al, 2010a), articular cartilage degeneration (Hsu et al, 2003), or cuff tear arthropathy (Neer et al, 1983). Clinical investigations have shown a correlation between two-tendon rotator cuff tears and secondary joint pathology (Keener et al, 2009), such as impaired joint function and LHB pain(Lakemeier et al, 2010a; Lakemeier et al, 2010b). Additionally, previous studies in a rat model have shown that in the presence of a two-tendon rotator cuff tear, joint function is altered (Perry et al, 2009b; Sarver et al, 2010) and the LHB tendon (Peltz et al, 2009), subscapularis tendon (Perry et al, 2009a), and glenoid articular cartilage (Reuther et al, 2012) display decreased mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…These changes could be the pathogenic precursor of a subsequent tear or a tendinopathic process occurring in the rupture area and extending to the portion of the tendon medial to the site of rupture. Lakemeier et al (13) showed that MMPs 1, 3, and 9 were also increased in degenerated long head of the biceps tendon in the presence of rotator cuff tears. TIMPs 1, 2, and 4 are present in the tissue matrix and in the blood, while TIMP3 is present only in the ECM.…”
Section: J Ointsmentioning
confidence: 99%